Comparative Effectiveness of Integrated Neuromuscular Inhibition Technique Along with Conventional Treatment Vs Conventional Treatment Alone in Patients of Knee Osteoarthritis - Fajr Ejaz, Maryam Safdar, Hina Ejaz (Pakistan Journal of Medical & Health Sciences, 2023)
Background: Due to cartilage damage adduction movement increased at knee joint which alters biomechanics of knee joint. All muscles attached to knee joint get overstretched, tightened and trigger points formed in them produces pain and alters functioning of knee joint. Objective: To determine which treatment approach either integrated neuromuscular inhibition technique INIT combined with conventional treatment or conventional treatment alone was effective in reducing pain, improving ROM and quality of life in patients with knee osteoarthritis. Material and Methodology: A randomized clinical trial was conducted on n=28 patients (23 females, 5 males) with age group of 45-70 years were randomly allocated into 2 groups. Group A received conventional treatment along with INIT technique and group B received conventional treatment alone, treatment was given for 2 weeks with 3 sessions / week. NPRS was used to measure pain at baseline, after 1st, 2nd, 4th and 6th session of treatment. ROM through goniometer measured at baseline, after 1st and at end of 2nd week (6th session). WOMAC scale for quality of life improvement measured at baseline and at end of 2nd week (6th session). SPSS version 20 was used for data analysis. Results: In-Between group analysis showed significant difference exist in knee pain and WOMAC scale values. However no, significant difference exist between both groups for knee flexion and extension except for knee extension range, improved after 6th session. Conclusion: Reduction in knee pain and disability of patient along with improved knee ROM was remarkably noted in the patients who received INIT technique combined with conventional treatment. Keywords: Osteoarthritis, trigger points, INIT technique, conventional treatment, Integrated Neuromuscular Inhibition Technique Ethical Approval Number: TUF/IRB/178/2023